PENERAPAN TUJUH KEBIASAAN ANAK INDONESIA HEBAT DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA PADA KONTEKS PENDIDIKAN KONTEMPORER - Khoiri Nur Afifah Jatiningrum; Dwi Anggraeni Siwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation and analyze the impact of the Seven Habits of Great Indonesian Children program on the formation of students’ disciplinary character in the context of contemporary education at SDN Jatiwarno 03, Karanganyar Regency. This research used a descriptive qualitative approach with data collection techniques of direct observation, in-depth interviews, and documentation. The informants consisted of the school principal, a fourth-grade teacher, and six fourth-grade students. The results show that the program was implemented through structured daily habituation, the use of a Daily Habit Journal, teacher role-modeling, and scheduled activities such as Healthy Friday and orderly queuing in the Free Nutritious Meal program. The impact identified was multidimensional, including increased student independence in daily routines, a shift in discipline motivation from extrinsic to intrinsic, the extension of habits from school to home, and the emergence of collective self-regulation among students, with the main challenge coming from gadget influence and uneven parental support at home. It is concluded that the program has become a strong starting point in shifting students’ disciplinary character from supervision-based compliance toward more autonomous awareness.